FORCED HEAT EXCHANGE AND COOLING RATE AT WATER ATOMIZATION OF MELTS - Ternovyi , Yurii; Panova , Vira (Scientific Journal "Metallurgy", 2020)
The formation of powder particles during atomization of metal melts with high pressured water occurs under conditions of significant cooling rates which determine both the geometric shape of the particles and their microstructure. To obtain powders with desired properties, it is necessary to know the influence of heat transfer conditions on the speed of solidification of particles. Due to the fact that the atomization zone contains about 107 particles per 1 cm3 , it is impossible to experimentally determine the establishment of a particular heat transfer regime. The purpose of the work was to determine analytically the heat transfer regime when metal melt is atomized with high-pressured water as well as to analyze the effect of thermal physics of the atomization process on the solidification rate of metal droplets. The paper considers the features of heat transfer in a metal drop-water-gas phase system. Based on the analysis of the known laws and phenomena of heat and mass transfer, heat transfer coefficients and heat flux densities for different heat transfer modes are estimated. The contributions of the conductive, convective, and radioactive components of heat transfer are estimated. It is shown that the fraction of heat transfer by radiation is not more than 0.1%. Theoretically, the cooling of droplets in the bubble mode of water boiling is confirmed. For tool steel, the particle cooling rate calculated on the basis of the heat transfer coefficient under the developed bubble regime shows values of the order of 106 K/s, that explains the observed in practice formation of the cellular structure of powders at atomization by high pressured water and confirms the correctness of the presented calculations. The results can be used to justify the thermal conditions for the production of powders with different structures, including amorphous.